Academic Persistence for Students Involved in the Accelerated Education Program in Dadaab Refugee Camp - Arvisais, Olivier; Charland, Patrick; Audet, François; Skelling-Desmeules, Yannick (Refuge: Canada's Journal on Refugees, 2021)
The academic community has highlighted the lack of research into accelerated education programs (AEPs) in refugee camps. Furthermore, AEPs take different forms in different countries. Generally speaking, however, several AEPs in different parts of the world are known for their low attendance rates. Accordingly, this article presents the key barriers causing absenteeism or preventing students from continuing their education within the program in Dadaab Refugee Camp. Our study shows that humanitarian action itself plays a significant role in pupil academic persistence. Also, flexible schedules are not a solution to absenteeism in AEP.